KEPEMIMPINAN KEPALA DESA DALAM MENINGKATKAN PARTISIPASI MASYARAKAT PADA PELAKSANAAN PEMBANGUNAN INFRASTRUKTUR DI DESA KWALABESAR KECAMATAN PALELEH KABUPATEN BUOL - U M. Armin, Sri Yanti; U. Ape, Sitima (Jurnal Administrasi Negara dan Ilmu Pemerintahan, 2022)
This study aims to identify and analyze "Village Head Leadership in Increasing Community Participation in Kwalabesar Village. This research uses a qualitative approach with a descriptive type. Data collection techniques using observation sheets or direct interviews with respondents. The results of this study are that the construction of road infrastructure in the village of Kwala Besar has not been running as it should. And community participation in road construction activities in the village of Kualabesar is still very low. So the results of the Village Head's leadership research in Kwalabesar Village have not yet built productive collaboration between the village government and the community. this means that the village government has not been able to encourage the community to actively participate in infrastructure development productively in good cooperative bonds. The conclusion of this study is that there are two indicators that have been running but not optimal, namely influencing society and achieving organizational goals. While indicators that have not been effective is productive cooperation. Where based on research findings that because road construction work is hampered, it makes people lack confidence and no longer want to participate in infrastructure development in the village of Kwalabesar. So that the community lacks trust and no longer wants to participate in development in the village. This means that the village head's leadership style has not succeeded in creating an atmosphere of productive cooperation between the government and the people in the village